Preclinical evaluation of Sesbanian grandiflora flower extract for antihyperlipidimic and antiobesity activity on experimental rats - Nikam, Sandhyarani Anil; Kolhe, Swati U.; Tembhurne, Sachin V. (Journal of Drug Delivery and Therapeutics, 2019)
Obesity is a chronic disorder of global prevalence and associated with morbidity and mortality. So the attention is being focused on the investigation of plant based drug  used in the traditional  medicine for the treatement of  obesity .The present study is undertaken to evaluate the anti- hyperlipidimic and anti-obesity activity of Sesbania  grandiflora flower extract in High Fatty Diet induced Obesity in rats.  Female wistar rat weighing 150-200 g were divided into different groups i.e. normal control, Negative control [Hfd control], orlistat [STD control], extract of sesbania grandiflora flower contain 200mg/kg and 400mg/kg group. .Obesity was assessed by measuring biochemical parameters such as glucose, triglyceride, serum cholesterol, HDL [High Density Lipoprotein], LDL [Low Density Lipoprotein] level. The results of the present investigation demonstrated that, the extract of sesbania grandiflora flower at 200mg/kg and 400 mg/kg shows significant protective effects on biochemical parameters such as body weight, BMI, obesity index, and adiposity index respectively as compared to HFD [High Fatty Diet] control group. Similarly, serum glucose, triglyceride, total cholesterol HDL, LDL was found to be attenuated as compare to HFD control group. The ethanolic extract of sesbania grandiflora flower exhibit significant anti-hyperlipidemia and anti- obesity activity in High fatty diet induced in obese rat.Keywords: HFD [High fatty diet], sesbania grandiflora flower extract, anti- obesity, Anti –Hyperlipidimic Activity.